Benthic trace metal fluxes in a heavily contaminated bay in China: Does the sediment become a source of metals to the water column?. (February 2020) - Li, Li; Zhen, Xiaotong; Wang, Xiaojing; Ren, Yijun; Hu, Limin; Bai, Yazhi; Liu, Jihua; Shi, Xuefa
Abstract: Over three different seasons, seawater, porewater and sediment samples were collected from Jinzhou Bay, a previously heavily contaminated bay, to quantitatively assess the benthic flux of trace metals after a reduction in fluvial/sewage discharge for almost three decades. The spatial distribution patterns of trace metals in seawater, surface sediment, as well as the vertical distribution patterns of metals in porewater and solid phases in short sediment cores were reported. Metal concentrations in seawater and sediment all showed much higher Cd and Zn concentrations inside the Jinzhou Bay compared to the rest of Bohai Sea area. Zn, Ni, Pb and Co all had average benthic fluxes coming out of the sediments to the water column, contributing about 0.5%, 0.3%, 1.4% and 14% to their current standing stock in Jinzhou Bay. Seasonal difference was also identified in seawater and porewater, as well as in the benthic fluxes. In general, benthic fluxes and porewater concentrations all tended to be higher in summer, implying a close relationship between benthic flux and the temperature-dependent organic matter degradation process at the sediment-water interface. Currently, there are clearly still other sources, possibly fluvial/sewage discharge, as the main source of trace metals in Jinzhou Bay waters. For Cd and Cu, concentrations in the water column remain high on an annual basis indicating that sediment still acts as a sink. Conversely, for Pb, Zn, Co, and Ni, the sediment is beginning to act as a source to the water column. Although this may not yet be significant, it will become more and more important with time, and can last for hundreds to thousands of years. Graphical abstract: Image 1 Highlights: Zn and Cd are identified as the two polluted metals in seawater and sediments. Pb, Zn, Co, Ni have average benthic fluxes coming out of sediment to the waters. The sediment in Jinzhou Bay still acts as a sink for Cu and Cd. Metal concentrations in porewater and benthic flux are relatively higher in summer. Benthic flux accounts for 0.3%–14% of the dissolved metal stocks in seawater.